Pathogenicity of Duck-Originated H9N2 Influenza Viruses on Chickens - Kunkun Zhao; Chunxia Jin; Yuxin Huang; Haiyang Zhang; Jingjing Xue; Hui Tian; Yue Yuan; Xiangdong Li; Wujie Liu; Kegong Tian (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Background: The spreading of H9N2 avian influenza viruses in poultry in Eurasia and Africa accompanied with the great economic losses to poultry industry in past decades has attracted the great attention of whole world. Domestic ducks play a critical role in the ecology of avian influenza viruses. Methods: In this study, 6 strains of H9N2 viruses were isolated from ducks and were valuated for the pathogenicity on chickens. The infected chickens were observed for 10 days and tracheal and cloacal swabs were collected for virus shedding detection. Results: All 6 isolates showed low pathogenicity to chickens. Clinical signs were not observed during 10 days in any of the infected chickens. While viruses were recovered from most of the infected chickens, and at least 4/5 chickens in each group shed virus even at 7 days post infection. Conclusion: Chickens infected with duck-originated H9N2 avian influenza viruses shed viruses for at least 7 days which provides a wide window period for virus transmission.